(untitled) (Revista Investigación & praxis en CS Sociales, 2023)
The study investigated the impact of collaborative learning on the development of reading skills. Gaps were found in the development of these skills among students, and collaborative learning was used as a framework to address them. The main objective was to explore how collaborative learning can affect the development of reading skills. The strategies used were analyzed, their impact on reading skills was assessed, and factors that could facilitate or hinder their effective implementation were identified. A qualitative methodology was employed, including interviews, observation, and document analysis. The results showed that collaborative learning can improve reading comprehension and fluency. However, challenges in its implementation were also identified, such as the need for effective facilitation and adaptation to individual needs. The study provided important information about the role of collaborative learning in reading skills and offered guidelines for pedagogical practice and future research.